Code parameter estimation from noisy data : TPC - Swaminathan, Ramabadran (2020)
A novel algorithm has been proposed for the blind estimation of two-dimensional turbo product code (TPC) parameters over noisy channel conditions. The performance of the algorithm is investigated for different code dimension values.